Optimization of the virtual mouse HeadMouse to foster its classroom use by children with physical disabilities - Teixido, Merce; Palleja, Tomás; Tresanchez, Marcel; Font, Davinia; Moreno, Javier; Fernández, Alicia; Palacín, Jordi; Rebate, Carlos (ADCAIJ: Advances in Distributed Computing and Artificial Intelligence Journal, 2013)
This paper presents the optimization of a virtual mouse called HeadMouse in order to foster its classroom use by children with physical disabilities. HeadMouse is an absolute virtual mouse that converts head movements in cursor displacement and facial gestures in click actions. The virtual mouse combines different image processing algorithms: face detection, pattern matching and optical flow in order to emulate the behaviour of a conventional computer mouse. The original implementation of HeadMouse requires large computational power and this paper proposes specific optimizations in order to enable its use by children with disabilities in standard low cost classroom computers.